Estimation and forecast of changes in the hydrochemical status of the Tisza river - Vasilenko, Lesya O.; Zhukova, Olena G.; Kokitko, Angelina A. (ІТГІП, 2018)
The engineer-ecological indexes and their parameters are used at the ecological estimation of the status of hydroecosystems (HE) of the Tisza water basin. The system-basin approach of research of the water basin bazed on the systematization and processing of environmental monitoring data for the long-term period was used. Such period allowed to set scientific conformities of the development of naturally-anthropogenic hydroecosystems in the conditions of constant technogenic load on them.
Keywords: water system; biotic communication; hydroecosystem; 504.453(477.87); 556.51(477.87)